RISK â BASED AUDIT ATAS SIKLUS PENDAPATAN PADA PT. SUPRANUSA INDOGITA - Rahmadi, Dimas; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
In the free trade era, Indonesia has great potencyto become prospective market for companies in running their business because it is supported by high power consumptive society. The company goals might fail, if the risk management processdoes not run effectively. It shows how importantthe risk management and the role of internal audit for a company in order to survive in encountering the environment turbulence or even the tight competition. This research is meant to develop therisk based audit method on revenue cycleat PT SupranusaIndogita. By using risk based audit, when the risk is getting high, the attention that is needed is getting high as well, so it can assure that the risk adequacy on a company has been managed in accordance with risk limit which has been determined by the company. The field study has been applied as the method and the data collection technique has been carried out by conducting observation, interview, and inspection. The result of the research shows that risk source is lied on the weak correlation of a system or procedure (process, human resources or internal control), unconducivework environment and some loose policies in dealing with the emerging problems which has great potencyto influence the security of company assets, the reliability of report and information which is related to the financial andits functional efficiency and effectiveness in using companyresources.Keywords: Internal Audit, Risk Based Audit, Risk Sources